Pharmacoeconomics of obesity in China: a scoping review - Chen, Zhuo; Jiang, Shan; Wang, Youfa; Khan, M. Mahmud; Zhang, Donglan; Rajbhandari-Thapa, Janani; Li, Li (Taylor and Francis Ltd., 2021)
Background: With the growing rate of obesity and associated chronic conditions in China, there is a need to assess the health and economic burdens of obesity and examine the effectiveness of pharmaceutical, medical, and comprehensive weight-loss interventions. Areas covered: This article reviewed publications retrieved from PubMed and Google Scholar during 2010–2020 on pharmacoeconomic studies related to overweight and obesity in China. We identified five cost-of-illness studies and four cost-effectiveness analyses of weight-loss interventions, including bariatric surgeries and a comprehensive intervention program. Expert opinion: There is a lack of pharmacoeconomic analyses of obesity in China. Existing studies have often taken the health system perspective without accounting for productivity loss. Cohort studies and studies based on electronic health records or claims data are needed to provide the epidemiologic parameters required for homegrown economic evaluations of the health and economic burdens of obesity in China, as well as the cost-effectiveness of interventions to reduce obesity and its sequela.